Bacteria and fungi of the lung: allies or enemies? - Garaci, Enrico; Pariano, Marilena; Nunzi, Emilia; Costantini, Claudio; Bellet, Marina Maria; Antognelli, Cinzia; Russo, Matteo Antonio; Romani, Luigina (Frontiers in Pharmacology, 2024)
Moving from the earlier periods in which the lungs were believed to represent sterile environments, our knowledge on the lung microbiota has dramatically increased, from the first descriptions of the microbial communities inhabiting the healthy lungs and the definition of the ecological rules that regulate its composition, to the identification of the changes that occur in pathological conditions. Despite the limitations of lung as a microbiome reservoir due to the low microbial biomass and abundance, defining its microbial composition and function in the upper and lower airways may help understanding the impact on local homeostasis and its disruption in lung diseases. In particular, the understanding of the metabolic and immune significance of microbes, their presence or lack thereof, in health and disease states could be valuable in development of novel druggable targets in disease treatments. Next-generation sequencing has identified intricate intermicrobe association networks that comprise true mutualistic or antagonistic direct or indirect relationships in the respiratory tract. In this review, the tripartite interaction of bacteria, fungi and the mammalian host is addressed to provide an integrated view of the microbial-host cross-talk in lung health and diseases from an immune and metabolic perspective.